2007
DOI: 10.1182/blood.v110.11.1286.1286
|View full text |Cite
|
Sign up to set email alerts
|

Induction with Fludarabine, Cyclophosphamide and Rituximab as Front-Line Therapy Against Follicular Lymphoma: Results from a Cooperative Spanish Trial

Abstract: Background and objective Fludarabine in combination with cyclophosphamide (FC) plus rituximab (R) is an effective treatment for newly diagnosed as well as relapsed follicular lymphoma (Tam 2004; Keating 2005; Sacchi 2007). Maintenance treatment with R, after different induction treatments, improves overall and progression-free survival (Forstpointner 2006; van Oers 2006). Therefore, we aimed to evaluate the efficacy and safety of the FC-R regime followed by maintenance doses of R. Patients and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Details of the findings from the included studies are provided in Table II. Nine studies were available for RCHOP in first-line therapy [26][27][28][29][30][31][32][33][34], two for RCHOP in the relapsed/refractory setting [10,35], five for RFlu in first-line therapy [36][37][38][39][40], and five for RFlu in the relapsed/refractory setting [40][41][42][43][44]. Only one study evaluating first-line RCVP met criteria for inclusion in the analysis [45].…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the findings from the included studies are provided in Table II. Nine studies were available for RCHOP in first-line therapy [26][27][28][29][30][31][32][33][34], two for RCHOP in the relapsed/refractory setting [10,35], five for RFlu in first-line therapy [36][37][38][39][40], and five for RFlu in the relapsed/refractory setting [40][41][42][43][44]. Only one study evaluating first-line RCVP met criteria for inclusion in the analysis [45].…”
Section: Meta-analysismentioning
confidence: 99%
“…To determine the relative contribution of PFS and QOL in our model, we performed a number of sensitivity analyses. We first varied the point estimates [26] Peer-reviewed 222 0.96 0.01 3-year PFS 75% Huang et al [27] Abstract only 102 0.86 0.01 -Hensel et al [28] Abstract only 69 0.90 0.01 -Ladetto et al [29] Peer-reviewed 68 0.62 0.03 4-year PFS 28% Ogura et al arm C [30] Peer-reviewed 32 0.94 0 Median 34.2 months Jager et al [31] Peer-reviewed 30 1.00 0 5-year PFS 59.4% Tomita et al [32] Peer-reviewed 21 0.76 0 2-year PFS 82% Niitsu et al [34] Peer-reviewed 15 1.00 0 2-year PFS 68.1% Economopoulos et al [33] Peer-reviewed 12 a 1.00 0 3-year PFS 60% RCHOP second-line therapy van Oers et al [10] Peer-reviewed 234 0.85 0.004 Median 33.1 months Domingo-Domenech et al [35] Peer-reviewed 16 0.88 0 18-month PFS 53% RFlu first-line therapy Vitolo et al [36] Abstract only 95 0.84 0 -Vitolo et al [37] Abstract only 80 0.90 0.01 3-year PFS 50% McLaughlin et al [38] Abstract only 76 1.00 0 3-year PFS 77% Tomas et al [39] Abstract only 69 0.97 0.03 -Tam et al [40] Peer-reviewed 7 1.00 0 3-year PFS 100% RFlu second-line therapy Forstpointner et al [41] Peer-reviewed 67 a 0.96 0.03 Median 3.9 years Sacchi et al [42] Peer-reviewed 54 0.90 0 4-year PFS 60% Hagemeister et al [43] Abstract only 39 0.95 0 2-year PFS 66% Leo et al [44] Peer-reviewed 17 0.88 0 -Tam et al [40] Peer-reviewed of treatment-related parameters over the broad range of values from heterogeneous individual studies reported in the literature. We observed that variation in the first-line PFS for RCHOP or RFlu within the range of published values did alter the optimal strategy of the model.…”
Section: Markov Decision Modelmentioning
confidence: 99%